2x-(x-1)=3+x

Simple and best practice solution for 2x-(x-1)=3+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(x-1)=3+x equation:


Simplifying
2x + -1(x + -1) = 3 + x

Reorder the terms:
2x + -1(-1 + x) = 3 + x
2x + (-1 * -1 + x * -1) = 3 + x
2x + (1 + -1x) = 3 + x

Reorder the terms:
1 + 2x + -1x = 3 + x

Combine like terms: 2x + -1x = 1x
1 + 1x = 3 + x

Solving
1 + 1x = 3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1 + 1x + -1x = 3 + x + -1x

Combine like terms: 1x + -1x = 0
1 + 0 = 3 + x + -1x
1 = 3 + x + -1x

Combine like terms: x + -1x = 0
1 = 3 + 0
1 = 3

Add '-1' to each side of the equation.
1 + -1 = 3 + -1

Combine like terms: 1 + -1 = 0
0 = 3 + -1

Combine like terms: 3 + -1 = 2
0 = 2

Simplifying
0 = 2

Combine like terms: 0 + -2 = -2
-2 = 2 + -2

Combine like terms: 2 + -2 = 0
-2 = 0

The solution to this equation could not be determined.

See similar equations:

| .75x-16=2(x-3)+4 | | 8(4+x)=72.00 | | 6n-3+2n=-1 | | 20(4r-48)= | | 2x+3-2x=2x+7 | | 7(x+1)=6(x-3) | | 11x=7x+72 | | 3x+4(2x+1)=26 | | 12x^2-52x-9=0 | | -x^2+18x-45=0 | | 1783x-2x=37x-12 | | 2x-20i=8*4y | | 5h+7=19 | | 2x+7=x+29 | | c(2x-d)=4c | | 3-x+7=19 | | .4w-11=-3 | | 4(5r+45)= | | 2,236,000+(-17.740x)=3,500,000 | | a^2-3ax+2ap-6=0 | | 5(x-3)=2(x-5) | | 11*i=0 | | 6(53+x)=x+2 | | 1/3(x-6)=4x-2/5(2-x) | | 53+x=6(x+2) | | 10+3y=90 | | 5x-19-3=-7 | | 3x=1x-6 | | 2(1+2x)=-6+3x | | 2x+56+4x-2=90 | | -a^2-6a=0 | | 2x+25=90 |

Equations solver categories